Assessment of occupational stress among certified registered anesthetists in the Greater Accra region - Sabblah, Dorcas Edem; Salifu, Abdulai Mohammed; Owusu, Richmond; Bawua, Serwaa Akoto (Frontiers in Public Health, 2024)
Background Work-related stress is a prevailing concern within the community of Certified Registered Anesthetists (CRAs), significantly impacting both the health and professional performance of these individuals. This study aimed to assess work-related stress and its influencing factors among CRAs practicing in the Greater Accra region was examined. Methods Using convenience sampling techniques, data were gathered from 140 participants via a Google form questionnaire distributed through WhatsApp. Descriptive statistics were employed to analyze the collected data, focusing on frequencies and proportions for categorical variables. For continuous variables, bivariate analysis (Chi-square) and ordinal logistic regression were conducted using STATA 16. A p-value <0.05 was considered significant. Results Among the 140 CRAs, 20 individuals (14.3%) reported experiencing mild stress levels according to the Weiman Occupational Stress Scale. Approximately 3 out of 4 CRAs (73.6%) reported having moderate stress levels, and 12.1% reported severe stress levels. This indicated that the majority of CRAs experienced moderate levels of stress, which was notably affected by the type of health facility and the use of inadequate or sub-standard equipment in the hospitals. Conclusion Based on these findings, the study recommends educational programs and counseling for CRAs to heighten awareness of the demanding nature of their job. Additionally, it suggests the provision of proper resources and standard equipment for CRAs. Facility-level motivation for CRAs is also advised to alleviate their stress. Finally, the study proposes further investigations into the factors contributing to work-related stress among CRAs.